Sand sharks eaudiobook Deborah knott mysteries series, book 15. - Maron, Margaret (Judge Deborah Knott, 2009)
Margaret Maron continues her best-selling Deborah Knott series with Sand Sharks-an "outstanding . neat mystery that [is] highly recommended" (Library Journal, starred review). Judge Deborah's hopes for relaxation at a seaside judicial conference are dashed when she stumbles upon the murdered body of a colleague. And when more judges turn up dead, Deborah fears she could be next.